The other ways of expressing condolence (other than R.I.P.) / Nazima Versay Kudus - Kudus, Nazima Versay (Academy of Language Studies, 2023)
As one the longest reigning monarchs, many grew up recognising her as the head of state of the UK and the Commonwealth. The demise of Her Majesty Queen Elizabeth II has saddened many people including fellow Malaysians. Thus, it is natural for people from all over the world and walks of life to express outpouring of condolence wishes to her family and the people of the United Kingdom of Great Britain and Northern Ireland. One of the common wishes is RIP, which is requiescat in pace in Latin or stands for Rest in Peace in English, often engraved on gravestones or written in obituaries. The use of 'rest in peace' has somewhat sparked a debate in the country - whether Muslims can offer such condolence to deceased non-Muslims. Mustafa Akyol, a Turkish scholar, asserts that Muslims can say "rest in peace" to non-Muslims who have passed away, adding that God's mercy is not confined to Muslims. According to Akyol, his viewpoint, which was also shared by other prominent theologians, was founded on two almost similar passages in the Quran, in Surah Al-Baqarah, verse 62 and Surah Al-Maidah, verse 69 where Allah says, "Indeed, the believers, Jews, Christians, and Sabians-whoever ˹truly˺ believes in Allah and the Last Day and does good will have their reward with their Lord. And there will be no fear for them, nor will they grieve".